ACKNOWLEDGE JURIDICAL REVIEW ON THE INFLUENCE OF COMPLETE SYSTEMATIC LAND REGISTRATION - Fitrianto, Bambang (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Land as a means to meet basic human needs has an important meaning and a very basic role in achieving the welfare of human life, both as individuals and as social beings. Humans as social beings who always make relations with the earth including the wealth contained therein, including land, so that intervention from the Government is needed, especially in the aspect of land which is very closely related to the national economy. This research uses descriptive research, qualitative research type, and uses empirical juridical research with a sociological approach, and this research uses field data collection methods (field research). As for writing this thesis, the writer argues that the implementation of Complete Systematic Land Registration (PTSL) in Batang Beruh Village has a positive effect on the high interest of the community to participate as participants, and also influences the creation of orderly land, especially orderly law and orderly administration, as well as influencing the increase economy and people's standard of living with easy access to banking capital.